FRI0070 High Prevalence of Subclinical Cardiovascular Disease and Abnormal Left Ventricular Geometry Detected by CMR in Asymptomatic Rheumatoid Arthritis Patients. (10th June 2014) - Bissell, L.-A.; Erhayiem, B.; Hensor, E.M.A.; Plein, S.; Emery, P.; Greenwood, J.P.; Buch, M.H.; Andrews, J.
Abstract : Background: Cardiac MRI (CMR) has merit in the assessment of cardiovascular disease (CVD) with increased left ventricular mass/end-diastolic volume (LVmass/EDV) associated (ass.) with greater CV risk.[1] CMR-RA studies are few; unclear if CMR assessments are applicable to RA. Objectives: To describe and quantify CV risk and sub-clinical CVD in an asymptomatic (CVD perspective) established RA cohort, using gold standard CMR-measured outcomes and a clinically deliverable comprehensive CV assessment. Methods: 78 RA patients (pts) (1980 ACR criteria) with disease >5yrs, no CVD/diabetes, assessed for traditional CV risk factors (RFs), RA profile, pulse wave velocity (PWV), and a subset of 58; non-contrast 3.0T CMR reported by CMR cardiologists. 10yr JBS CV risk scores calculated (x1.5 if required)[2, 3]. Univariable analysis (UVA) variables marked* in Table 1 . CMR values (exc. LVEF) adj. for body surface area (BSA); "abnormal" values adj. for age/sex[4]. Results: 73% were female, mean (SD) age 60 (9.3)yrs, 91% white British (RA profile in Table 1 ). JBS risk: median (IQR) 13.3 (7.4, 20.8)%; 16 (22%) pts >20% (only 5/16 were on primary prevention therapy). Only age (B0.065, p=0.001) and syst. BP (B0.036, p<0.001) were ass. with higher PWV on multivariable analysis (MVA) (R 2 0.482). CMR abnormalities were common (Table 1 ). Greater LV mass/BSA was ass. with male gender, HTN, ever-smoking, waist/hip ratio (WHR); only gender (B13.519, p<0.001) and HTN (B5.658 p=0.003) sig. on MVA (R 2 0.643). Greater LVmass/EDV was ass. with male gender, age, HTN; only gender (B0.064, p<0.001) and HTN (B0.039, p=0.012) sig. on MVA (R 2 0.411). 59% had reduced LV mass/BSA, more common in females (69% vs. 38% males, p=0.038). LVmass/EDV was reduced referent to published controls [5]; lower in females (p<0.001). No RA variables were ass. with PWV/CMR measures. Conclusions: CMR-detected subclinical CVD abnormalities are common in asymptomatic RA pts and ass. with traditional CV RFs. Despite enhanced CV risk in RA, we demonstrate reduced LV mass/BSA and LVmass/EDV, similar to the only other comparably sized CMR-RA study.[5] This suggests usual LV geometry interpretations may not apply to RA and implies complex mechanisms, with perhaps different compensatory remodelling in RA; warranting further study. References: JACC Card Img 2010; v3i6. Heart 2005:91:S5. ARD 2010; 69v2. www.cmr-guide.com . A&R 2010; 62v4. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4079